Biological turnover of DMS, DMSP and DMSO in contrasting open-sea waters - Simó, Rafel; Pedrós-Alió, Carlos; Malin, Gillian; Grimalt, Joan O. (Marine Ecology Progress Series, 2000)
11 pages, 2 figures, 3 tables Speciation and turnover of the methylated sulfur compounds dimethyl sulfide (DMS), dimethylsulfoniopropionate (DMSP) and dimethyl sulfoxide (DMSO) were studied in waters of the open western Mediterranean, the near-coastal North Sea and the subpolar North Atlantic, with chlorophyll a concentrations spanning 2 orders of magnitude (0.12 to 13 μg 1-1>). Particulate DMSP (DMSP(p): 5 to 340 nM) was the predominant pool in most waters. Dissolved and particulate dimethyl sulfoxide were alsofound at significant concentrations (DMSO(d): 2 to 25 nM, DMSO(p): 3 to 16 nM). Biological DMSP consumption rates were estimated from the time course of total (dissolved + particulate) DMSP Concentration in dark incubations Dimethyl sulfide production and consumption rates were determined by the 'inhibitor addition' method. High DMS production and consumption rates were found during a bloom of Phaeocystis sp. in North Sea waters. In all samples, turnover time constants for total DMSP and DMS were of the same order, ranging from 0.7 to 5.4 and from 0.3 to 2.1 d, respectively. DMS formation was the fate for 9 to 96% of the DMSP consumed. Use of chloroform as an inhibitor gave estimates of DMS production and consumption rates approximately 70% higher than those obtained with dimethyl disulfide and dimethyl selenide. In some incubation experiments, the time course of DMSO concentration has been followed along with DMS and DMSP for the first time. Evidence for active biological cycling (production and consumption) of DMSO in seawater is presented Peer Reviewed